Evaluasi Teknis dan Ekonomis dalam Merencanakan Penggantian Alat Angkut pada Pengupasan Overburden di PT Citra Mitra Sehati Site Job PT Bama Ketahun Desa Tanjung Dalam, Kecamatan Ulok Kupai, Kabupaten Bengkulu Utara, Provinsi Bengkulu - Dandi Leroy Tandri; Iswandaru; Indra Karna Wijaksana (Bandung Conference Series: Mining Engineering, 2023)
Abstract. In its production activities, PT Citra Mitra Sehati uses 1 unit of Doosan Dx 500 diggers which have been used for production for 2 years, and 5 units of the new ADT Volvo A40E hauling equipment which has been in operation for 8 years. The condition of mechanical devices that are classified as old and unfit for operation because they often break down and require special maintenance and the greater the operating costs of the equipment, of course affects productivity and production which will decrease. Therefore, so that the mining activities carried out are not disturbed due to equipment problems that are often damaged, it is necessary to replace the equipment. In planning the replacement of mechanical devices, it is necessary to carry out technical and economic studies. For technical studies, it includes studies on the production of equipment, as well as for economic studies, it includes operating costs, ownership costs, Present Worth Cost values and Production Unit Cost values. The purpose of this study was to determine the comparison of the production of old equipment and new equipment, and economic comparisons including operating costs, ownership costs, Present Worth Cost and Production Unit Cost values. The research method used in this research includes the collection of primary data and secondary data. The primary data in this study are working time, volume of excavator bucket material, circulation time, holding time, in-situ density testing, density loose testing, and haul road data. Secondary data in this study are equipment specifications, fuel prices, lubricating oil prices, filter prices, tool life, trade in value, depreciation, tax and insurance, inflation, and interest rates. From primary and secondary data, it is calculated so as to get the results of production values, operating costs, ownership costs, Present Worth Cost and Production Unit Cost for old equipment and new equipment. From the results of a technical study conducted, the old conveyance has a work efficiency of 82.09% with a production of 916.135,48BCM/year, while the new conveyance has a work efficiency of 85.53% with a production of 1,131,547.20 BCM/year. The results of the economic study showed that the operating costs of the old transportation equipment were IDR 3,241,306,604.79/year, and the operating costs for new transportation equipment were IDR 2,537,653,411.82 / year. In addition, the results of the calculation of the Production Unit Cost of the old transportation equipment were Rp. 7.365,17/BCM while for the new transportation equipment, it was Rp. Rp 2.725,38/BCM. Based on the results of the technical and economic studies, the digging and loading equipment needs to be replaced because the productivity of the new equipment is higher and has lower operating costs than the old equipment. From the calculation of the Unit Cost Production, it is known that the new digging-loading and hauling equipment is more economical than the old equipment, and has a better long-term investment. Abstrak. PT Citra Mitra Sehati dalam kegiatan produksinya, menggunakan alat gali-muat Doosan Dx 500 sebanyak 1 unit yang telah digunakan untuk produksi selama 2 tahun, dan 5 unit alat angkut ADT Volvo A40E baru yang sudah beroperasi selama 8 tahun. Kondisi dari alat mekanis yang sudah tergolong tua dan tidak layak beroperasi karena sering terjadi kerusakan dan membutuhkan perawatan yang khusus serta biaya operasi alat semakin besar, tentunya mempengaruhi produktivitas dan produksi yang akan semakin menurun. Oleh karena itu agar kegiatan penambangan yang dilakukan tidak terganggu karena masalah alat yang sering mengalami kerusakan maka perlu dilakukan penggantian alat. Dalam merencanakan penggantian alat mekanis maka perlu dilakukan kajian secara teknis dan ekonomis. Untuk kajian teknis meliputi kajian produksi alat, serta untuk kajian ekonomi meliputi biaya operasi, biaya kepemilikan, nilai Present Worth Cost serta nilai Production Unit Cost. Tujuan penelitian ini adalah mengetahui perbandingan produksi alat lama dan alat baru, dan perbandingan secara ekonomis meliputi biaya operasi, biaya kepemilikan, nilai Present Worth Cost dan nilai Production Unit Cost. Metode penelitian yang dilakukan dalam penelitian ini meliputi pengambilan data primer dan data sekunder. Data primer pada penelitian ini yaitu waktu kerja, volume material bucket excavator, waktu edar, waktu hambatan, pengujian density insitu, pengujian density loose, dan data jalan angkut. Data sekunder pada penelitian ini yaitu spesifikasi alat, harga bahan bakar, harga minyak pelumas, harga filter, umur alat, nilai trade in value, depresiasi, tax and insurance, inflasi, dan tingkat suku bunga. Dari data primer dan sekunder dihitung sehingga mendapatkan hasil nilai produksi, biaya operasi, biaya kepemilikan, Present Worth Cost dan Production Unit Cost untuk alat lama dan alat baru. Dari hasil kajian teknis yang dilakukan, alat angkut lama mempunyai efisiensi kerja 82,09% dengan produksi sebesar 916.135,48 BCM/tahun, sedangkan untuk alat angkut baru mempunyai efisiensi kerja 85,53% dengan produksi sebesar 1.131.547,20 BCM/tahun. Hasil kajian ekonomi didapatkan biaya operasi alat angkut lama sebesar Rp 3.241.306.604,79 /tahun, dan untuk biaya operasi alat angkut baru adalah sebesar Rp 2.537.653.411,82 /tahun. Selain itu didapatkan juga hasil perhitungan Production Unit Cost alat angkut lama yaitu sebesar Rp 7.365,17/BCM BCM sedangkan untuk alat angkut baru yaitu sebesar Rp 2.725,38/BCM. Berdasarkan hasil kajian teknis dan ekonomis tersebut, maka alat gali-muat dan alat angkut perlu diganti karena produktivitas alat baru lebih besar dan memiliki biaya operasi lebih hemat dibandingkan alat lama. Dari hasil perhitungan Unit Cost Production diketahui alat gali-muat dan angkut baru lebih hemat dibandingkan alat lama, serta memiliki investasi jangka panjang yang lebih baik.